Increasing Political Participation and Capacity of Indigenous Papuans: Encouraging Adaptive Collaborative Governance - Iswandi, Kelik (Jurnal Review Politik, 2023)
This paper delves into the potential of collaborative governance in addressing conflict resolution in Papua, focusing on the marginalized Indigenous Papuans (OAP) affected by shifting management policies. The conflict stems from historical injustices and capacity disparities between OAP and non-OAP. It aims to introduce collaborative governance, emphasizing reconciliation and adaptive approaches, particularly capacity building, and identifies potential implementation hurdles. Using normative research methodology with secondary data, the hypothesis proposes enhancing OAP capacity and participation to facilitate collaborative processes. Despite LPDP scholarships' ineffectiveness, a structured roadmap is essential for fostering collaborative governance. Furthermore, engaging the private sector is crucial, leveraging its information-seeking capabilities to enhance program efficacy. Collaboration with the private sector should align with OAP interests, aiding capacity building through education and training initiatives